Study on Long-Term Variation Characteristics of Geomagnetic Cutoff Rigidities of Energetic Protons Caused by Long-Term Variation of Geomagnetic Field - Chu, Wei; Yang, Yanyan; Xu, Song; Qin , Gang; Huang, Jianping; Zeren, Zhima; Shen, Xuhui (Frontiers in Earth Science, 2022)
As a parameter that quantitatively measures the shielding effect of the earth’s magnetic field on energetic particles, the geomagnetic cutoff rigidities will change significantly with the long-term change of geomagnetic field. In this paper, by using the numerical simulation method, combined with the variation trend of the earth’s internal field IGRF model and the energetic particles windows (EPWs), the variation characteristics of the cutoff rigidities of geomagnetic energetic particles in the vertical direction from 1965 to 2025 were studied. The study found that, there is a close relationship between the cutoff latitude corresponding to the cutoff rigidities and the background magnetic field intensity, but they are not a simple linear relationship. The changes of the cutoff rigidities and geomagnetic field in the northern and southern hemispheres are asymmetric. The weakening of the geomagnetic field will push the cutoff latitudes towards the near equatorial region in the southern hemisphere, but for northern hemisphere the phenomenon is not always credible. In the northern hemisphere, the areas of EPWs will decrease at a relative rate of 0.03%/yr, but in the southern hemisphere, it will increase at a rate of about 0.05%/yr to 0.12%/yr. The long-time trajectory of the geomagnetic poles do not correspond to the positions of the central points of the EPWs. The study can be used for a long-term forecasting of cutoff rigidities caused by background geomagnetic field variations.